Gender, Skills and Educational Outcomes - Silva, Ana Paula Melo da (2016)
Why do girls and boys perform differently in school? In this paper, we examine the gender gap in educational achievement for Language and Mathematics using a novel dataset of 10,000 students in the Public School System of Sao Paulo, Brazil. The broad set of available information allows us to test the relative importance of skills and incentives to schooling on the educational outcomes of boys and girls. We summarize a unique socioemotional profile of boys and girls in Brazil and find significant gender differences in skills and incentives to schooling. Performing a decomposition exercise, we find that the gender gap in educational outcomes is significantly explained by differences in the levels of observed inputs, especially incentives to schooling. We bring new evidence on the importance of incentives to schooling in explaining the gender differences in both classroom grades in standardized test scores.